Editorial Arsir Vol.7 No. 1 (2023) - Kamil, Erfan M (Arsir, 2023)
Arsir: Journal of Architecture is a journal accredited by the Ministry of Research and Technology of Higher Education of the Republic of Indonesia. This journal consists of scientific articles as a result of research, conceptual papers, case study reports. This journal is registered with print number p-ISSN: 2580-1155 and digital e-ISSN: 2614-4034. This journal publication is managed by the Architecture Study Program, Faculty of Engineering, Universitas Muhammadiyah Palembang This is cover, editorial-reviewer team, and table of contents Arsir Vol.7 No.1 (2023) published in 30 June 2023